Peran Pengabdian dalam Kesuksesan Program Tahfizd di Pondok Pesantren MA Islamic Centre Binbaz - Amrin Mustofa; Eko Ngabdul Shodikin (At Turots: Jurnal Pendidikan Islam, 2022)
This study aims to add to the treasures of the service utilization system in learning tahfizdul quran at an educational institution. In addition, this research also aims as an evaluation material for program activities, to measure how big the role of devotion is for the success of the Tahfizdul Quran flagship program. This study uses a descriptive quantitative method, namely the author describes based on facts in the field at the Islamic Center Islamic Boarding School BINBAZ. The conclusion of this study is that the role of service is very large, both in helping learning, character building as well as, maturation of the memorization of the service itself so that it becomes the concern of the boarding school administrators to realize maximum monitoring to realize the success of the tahfizd program at Pon Pes Islamic Center Binbaz.